STUDENT ATTITUDES TOWARD THE USE OF FACEBOOK IN HIGHER EDUCATION: IMPLICATIONS FOR THE LEARNING EXPERIENCE - Marković, Marija R; Stanisavljević Petrović, Zorica (CM: Communication and Media ISSN 2466-541X; 2466-5452 (Online), 2024)
In light of the ongoing development of digital technologies and the emergence of new social networks, questions regarding the use of Facebook in higher education are becoming increasingly relevant. Consequently, there is a need to reconsider the application of Facebook as a tool for learning support and communication during the studying process. This research aimed to investigate students’ attitudes toward using the social network Facebook in university education. The study employed a descriptive method, with a rating scale used as the primary instrument. Data was collected from a sample of 314 undergraduate students at the Faculty of Philosophy in Niš. The research results indicate that students highly value the potential of Facebook in terms of exchanging information and sharing study materials, while they are generally reserved and cautious when it comes to using this social network for learning purposes. Regarding the independent variables of the study (study program, average grade, duration of social media presence, and frequency of access), it was found that there are statistically significant differences in respondents’ answers to certain items. The pedagogical implications of the research can be significant for improving and modernizing teaching in higher education through the use of Facebook, as well as other digital tools.